2006
DOI: 10.1038/sj.onc.1209474
|View full text |Cite
|
Sign up to set email alerts
|

Gain of 11q/cyclin D1 overexpression is an essential early step in skin cancer development and causes abnormal tissue organization and differentiation

Abstract: Non-melanoma skin cancers, in particular keratoacanthomas (KAs) and squamous cell carcinomas (SCCs), have become highly frequent tumor types especially in immunesuppressed transplant patients. Nevertheless, little is known about essential genetic changes. As a paradigm of 'early' changes, that is, changes still compatible with tumor regression, we studied KAs by comparative genomic hybridization and show that gain of chromosome 11q is not only one of the most frequent aberration (8/18), but in four tumors also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 40 publications
1
38
1
Order By: Relevance
“…Perhaps, uncoupling these processes may require deregulation of additional pathways. For example, dermal keratinocytes that overexpress CDK4 and p21, in addition to cyclin D1 lack terminal differentiation (19). Our data are in contrast with those from other cell types where CDK6 overexpression blocks differentiation (8)(9)(10)(11)(12).…”
Section: Discussioncontrasting
confidence: 56%
“…Perhaps, uncoupling these processes may require deregulation of additional pathways. For example, dermal keratinocytes that overexpress CDK4 and p21, in addition to cyclin D1 lack terminal differentiation (19). Our data are in contrast with those from other cell types where CDK6 overexpression blocks differentiation (8)(9)(10)(11)(12).…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, treatment with combinations of chemotherapy and radiation (Forastiere et al, 2003;Vermorken et al, 2007) might be affected by FADD expression due to 11q13 amplification, as hypothesized previously (Gibcus et al, 2007b). Because amplification was proven an early event in tumorigenesis (Izzo et al, 1998;Burnworth et al, 2006), and amplicons are inherited during tumorigenesis, we hypothesize that the high occurrence of 11q13.3 amplification enables multiple genes to be beneficial to tumour progression at distinct stages of tumour development.…”
Section: Discussion Cortactin Predicts Poor Survival In Late Stage Lamentioning
confidence: 63%
“…We previously showed that loss of chromosome 15 correlated with loss of the angiogenesis inhibitor TSP-1 which in turn correlated with the angiogenic switch required for malignant conversion (Folkman and Hanahan, 1991;Bleuel et al, 1999). We recently also showed that loss of chromosome 15 occurs in human skin carcinomas and that this correlated with progression from benign to malignant tumor phenotype (Burnworth et al, 2006). Accordingly, loss of chromosome 15 seen here, may also have provided a selective advantage and thereby contributed to the high frequency of tumorigenic conversion (three out of the four different HaCaT populations irradiated with 4 Â 5 or 1 Â 20 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 92%